Is there evidence for population regulation in amphibians and reptiles? - Muniz Leao, Suelem (2018)
From the 1950s to the present, many researchers have tested time series data for density dependence. All kinds of organisms have been studied, from microorganisms to insects and vertebrates to plants. A variety of techniques and population growth models were developed, and the conceptual framework to study populations has been improved. We searched for long time series data on amphibians and reptiles in the literature. From 102 population time series, and after filtering the dataset, we tested for density dependence in time series data for 69 populations (52 species) of amphibians (anurans and caudatans), serpents, lacertilians, chelonians, rhynchocephalians, and crocodilians. We used the exponential growth state-space model and the Ornstein-Uhlembeck state-space model as proxy models for density-independent and density-dependent population growth models, selecting between them with the parametric bootstrap likelihood ratio test. The hypothesis of density independence was rejected for 2 amphibians, 11 serpents, 3 chelonians, 1 rhynchocephalian, and 2 crocodilian populations. Detailed data for serpents and chelonians allowed identification of external factors such as changing food supplies and habitats as drivers of observed changes in population densities. We highlight the need of both long-term and experimental studies on reptile and amphibian populations in semipristine or preserved areas.